The combination of Lonicerae Japonicae Flos and Forsythiae Fructus herb-pair alleviated inflammation in liver fibrosis - Zhang, Jing-Bei; Jin, Hong-Liu; Feng, Xiao-Ying; Feng, Sen-ling; Zhu, Wen-Ting; Nan, Hong-Mei; Yuan, Zhong-Wen (Frontiers in Pharmacology, 2022)
Objective: To explore the active components and molecular mechanisms underlying the anti-inflammatory effects of Lonicerae Japonicae Flos and Forsythiae Fructus herb-pair (LFP) in carbon tetrachloride (CCl4)-induced rat liver fibrosis. Methods: The main active ingredients and disease-related gene targets of LFP were determined using TCMSP and UniProt, and liver fibrosis disease targets were screened in the GeneCards database. A network was constructed with Cytoscape 3.8.0 and the STRING database, and potential protein functions were analyzed using bioinformatics analysis. Based on these analyses, we determined the main active ingredients of LFP and evaluated their effects in a CCl4-induced rat liver fibrosis model. Serum biochemical indices were measured using commercial kits, hepatocyte tissue damage and collagen deposition were evaluated by histopathological studies, and myofibroblast activation and inflammation were detected by reverse transcription-polymerase chain reaction (RT-PCR) and western blotting. High-performance liquid chromatography-mass spectrometry was performed to determine the levels of homocysteine, reduced glutathione, and oxidized glutathione, which are involved in inflammation and oxidative stress. Results: The main active components of LFP were quercetin, kaempferol, and luteolin, and its main targets were α-smooth muscle actin, cyclooxygenase-2, formyl-peptide receptor-2, prostaglandin-endoperoxide synthase 1, nuclear receptor coactivator-2, interleukinβ, tumor necrosis factor α, CXC motif chemokine ligand 14, and transforming growth factor β1. A combination of quercetin, kaempferol, and luteolin alleviated the symptoms of liver fibrosis. Conclusion: The results of this study support the role of LFP in the treatment of liver fibrosis, and reveal that LFP reduces collagen formation, inflammation, and oxidative stress. This study suggests a potential mechanism of action of LFP in the treatment of liver fibrosis.